A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 11 PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Oktaviani, Etri; Gultom, Effendy; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is to find out the ability of the second year students of SMAN 11 Pekanbaru in comprehending Narrative texts. The number of population is 256 students divided into nine classes. The researcher used random sampling technique to determine the sample. The samples were 54 students. The needed data were taken from the students’ score in comprehending narrative texts. The test comprehends five narrative texts of which all text has eight items or 40 items all together. The time allocation was 120 minutes. The result of the study revealed that the mean score was 65.56 which indicated that the students were in good level of ability. The highest mean score (73.7) was in finding references. The lowest mean score (51.48) was in finding the meaning of vocabulary.Key Words: Students’ ability, Reading Comprehension, Narrative Texts